2004
DOI: 10.1080/09273970490489630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraoperative sponge mitomycin C and 5-fluorouracil on scar formation following strabismus surgery in rabbits

Abstract: MMC, and to a lesser extent 5-FU, are shown to be effective in reducing postoperative scarring following strabismus surgery in rabbits. It seems reasonable to suggest that antimetabolites should be used for cases having an increased risk of postoperative adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…The less-reflective surface of the AM (stromal side) was placed toward the muscle plane to handle the AM easily during surgery because the stromal side of the AM is relatively rough and adhesive, while the epithelial side of the AM is shiny and smooth. In addition, the fibrotic proliferation was expected to come from the subconjunctival fibroblasts [1, 9]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The less-reflective surface of the AM (stromal side) was placed toward the muscle plane to handle the AM easily during surgery because the stromal side of the AM is relatively rough and adhesive, while the epithelial side of the AM is shiny and smooth. In addition, the fibrotic proliferation was expected to come from the subconjunctival fibroblasts [1, 9]. …”
Section: Methodsmentioning
confidence: 99%
“…Due to the fact that the suppression of inflammation is a key element in the prevention of further fibrovascular proliferation and scar formation in the conjunctiva [3], various approaches have been used to reduce postoperative inflammation and scarring following strabismus surgery. Among these are mechanical barrier devices that isolate the muscle from the sclera and the Tenon's capsule, steroids, antiproliferative agents and viscoelastic substances [19]. However, none of these techniques has been widely accepted because of associated complications and inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…In that study we demonstrated that histopathologically Seprafilm significantly reduces the development of fibrosis in strabismus surgery. The reports on the benefit of the use of mitomycine C and 5-fluorouracil demonstrate some variability67131415. The use of such agents should be regarded with caution as they may also decrease the reattachment of the extraocular muscle to the scleral tissue.…”
Section: Treatmentmentioning
confidence: 99%
“…17 Mitomycin C (MMC), a well-known chemotherapeutic and antifibrotic agent, is also an extensively used topical agent for the prevention of postoperative fibrosis after ophthalmologic surgeries such as glaucoma filtering surgery, photorefractive keratectomy, and radial keratotomy, and the results have been successful. [18][19][20] In the literature, the effect of MMC on epidural fibrosis that develops in craniectomy area has not been evaluated yet. Based on the histological similarities between the sclera and dura mater, 21 we performed intraoperative local application of MMC in rats following craniectomy.…”
Section: Introductionmentioning
confidence: 99%